Neuro-leadership as a strategy for the strengthening of management in educational institutions - Atencio Bravo, Eduardo Alfonzo (2020)
Understanding management in educational institutions in the light of neurosciences, has given rise to the approach of the potential of the brain in favor of the exercise of leadership as an emerging strategy, therefore, this census study, focused on proposing strategies based on neurolide Leadership for the strengthening of said management in the Pueblo Bujo Educational Institution of the municipality of Montería, Córdoba-Colombia in 2017-2018. Methodologically, the article was framed in the empirical analytical paradigm of quantitative approach, through a type of projective research with field design - not experimental. The population consisted of 40 subjects belonging to the management and teaching staff of the institution in question, who were provided with informed consent, a questionnaire under the Likert scale with 33 items, whose reliability was calculated with the Crombach's Alpha formula, throwing 0.83. The study findings argue that the areas of focus of neurolide Leadership, the style of leadership assumed, and the managerial skills performed are acceptable; however, the management and emotional leadership exercised by the institution's management personnel are clearly needed, which demonstrates the need to formulate strategies with an emphasis on neuroplasticity, neuro-learning and the attentional capacity of those involved. The conclusions refer to an urgent reformulation of the strategic management exercise, where the emotional - affective factor must be reinforced against the cognitive - rational, asymmetry that shows disparity in the use of resources that enable the efficiency, effectiveness and effectiveness of the processes.